A novel algorithm L-NCD for redundant reader elimination in P2P-RFID network. Issue 2 (June 2017) - Xu, He; Shen, Weiwei; Li, Peng; Zhu, Jiawei; Wang, Ruchuan
With the development of radio frequency identification technology, radio frequency identification system has been deployed in different applications in a large scale. It needs a densely deployed reader environment to cover the work area, especially in radio frequency identification logistics and warehousing applications. If the distribution area and the number of readers are not optimized, and some of them will be redundant, which will reduce the efficiency of the whole radio frequency identification system. Researchers have proposed many algorithms and optimization techniques to solve the problem of redundant readers. In this paper, the authors propose a novel redundant reader elimination algorithm, namely, L-NCD, in P2P-RFID reader network, combined with layered eliminate optimization and neighboring coverage density. The simulation results demonstrate that the proposed algorithm eliminates more redundant readers than the other methods such as redundant-reader elimination under the same conditions.